Analysis of the sociodemographic and obstetric profile of mothers who died of fetal death in a high-risk maternity hospital - de Lima Castro, Patrícia Regina (2024)
Objective: to describe the sociodemographic and obstetric profile of mothers who had a fetal death in the months of September 2022 to September 2023, in a High Risk maternity hospital. Method: This is an epidemiological and retrospective study with a cross-sectional design, descriptive and with a quantitative approach, where sampling was based on medical records of mothers who had fetal deaths. Therefore, the study approach was based on convenience. For data analysis and processing, data were first entered into the Microsoft Excel for Windows-2010 program and then the Statistical Package for the Social Sciences (SPSS) software, version 20.0, was used. The research was submitted and approved by the Human Research Ethics Committee. 66 medical records were analyzed. Results: Regarding obstetric characteristics, 81.8% had already experienced other pregnancies, of which 74.3% had already experienced childbirth and 33.3% had miscarriages. 6.1% did not have any prenatal consultations and 43.9% had fewer than 6 consultations; 42.4% were between 37 and 41 gestational weeks at the time of death. Fetal hypoxia (22%) and hypertensive syndromes during or before pregnancy (19.6%) were the main causes of deaths analyzed. Conclusion: Thus, the need for integrated and personalized approaches to maternal health care is evident, emphasizing the importance of preventive and educational strategies that consider the diversity of socioeconomic, cultural and clinical factors involved in the scenario of fetal deaths.